Contributing to the development of social pedagogy in the UK: a case study at 'Santiago 1' residential care home in Spain - Paz Oliva, Víctor (The University of Edinburgh, 2021)
In recent years there has been a growing interest in social pedagogy in the UK, much of which has focused on residential care for looked after children, a system that has been under scrutiny over recent decades. Research carried out in other European countries where social pedagogy is an established academic discipline and profession, alongside pilot programmes, training courses and practical initiatives in the UK, have shed light on what not that long ago was an unknown field in this country. These European studies suggest that social pedagogical approaches might potentially help to improve residential care in the UK. This research aims to contribute to the development of social pedagogy in the UK through the study of its practice in Spain, where there is a significant tradition in this field. In order to do it, I have carried out a case study in a residential care institution working to a social pedagogic approach named “Santiago 1”. In a time when the tendency is to provide small family-like homes for children in care, Santiago 1 offers an example of a big institution (around 100 residents in total) where education, both in its more formal and informal versions, is at the core of their intervention. Through this case study, I have sought to find how its practice can inform a conceptualisation of social pedagogy and the possible implications of this for the current residential care situation in the UK. I designed an inductive study, using qualitative ethnographic methods (participant observation and semi-structured interviews) for data collection, followed by a thematic data analysis. The findings arguably make such desired contribution. The findings confirm some of the notions and principles already existing in the academic body of knowledge in the field of social pedagogy. However, they also give insight into aspects that are frequently overlooked, such as creating an educative intervention that goes beyond the target group to have an impact on the community, and making use of group work and living as a cornerstone for the social pedagogic intervention. These perspectives lead to a discussion in which I point out the implications of trying to implement these social pedagogic ideas and practices in the UK and argue for the need for several changes in the current residential care system and the regulations that frame it that would be required in order to do so.
Keywords: social pedagogy; residential child care